2015
DOI: 10.1002/lary.25495
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal lymph node involvement in human papillomavirus–associated oropharyngeal squamous cell carcinoma

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 17 publications
0
31
2
Order By: Relevance
“…With regard to oncologic outcomes, Tang et al demonstrated that RPLN involvement demonstrated a nonsignificant trend toward worse OS ( P = .08). Similarly, Baxter et al found increased odds of disease recurrence or death in patients with HPV‐associated OPC with radiographic RPLN involvement but this did not remain statistically significant in multivariate analysis . In contrast, Samuels et al found lower 5‐year rates of OS and increased distant failure in patients with RPLN involvement compared with those without, findings that maintained statistical significance on multivariate analysis …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With regard to oncologic outcomes, Tang et al demonstrated that RPLN involvement demonstrated a nonsignificant trend toward worse OS ( P = .08). Similarly, Baxter et al found increased odds of disease recurrence or death in patients with HPV‐associated OPC with radiographic RPLN involvement but this did not remain statistically significant in multivariate analysis . In contrast, Samuels et al found lower 5‐year rates of OS and increased distant failure in patients with RPLN involvement compared with those without, findings that maintained statistical significance on multivariate analysis …”
Section: Discussionmentioning
confidence: 98%
“…However, given that these patients had been treated prior to routine tumor HPV testing, the lack of tumor HPV status limited study conclusions. Since our initial publication, other single‐institution series evaluating patient outcomes for those specifically with HPV‐associated OPC and RPLN involvement have demonstrated mixed results …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis to the RPLNs is not a rare event in oropharyngeal SCC, occurring in 13%–36% of patients in studies examining the RPLN via histopathology. It occurs most commonly in tumors of the tonsil and lateral pharyngeal wall and seldom in tumors of the base of tongue . Few studies of the diagnostic accuracy of the various imaging modalities for the detection of RPLN metastasis have been conducted in which pathologic confirmation was available .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of retropharyngeal metastases has historically been associated with decreased local control and overall survival . However, several contemporary series have failed to demonstrate this effect, suggesting that multimodality treatment may mitigate the negative prognostic effect, or that the effect on prognosis may not be as significant in the human papillomavirus (HPV)‐positive oropharyngeal SCC population …”
Section: Introductionmentioning
confidence: 99%